ASSESSMENT OF TEMPOROMANDIBULAR DYSFUNCTION AND MANDIBULAR FUNCTIONAL IMPAIRMENT IN DENTISTRY ACADEMICS - Guimarães, Élcio Alves; Goulart, Tathiane Tavares; Makhoul, Kelly Duarte Lima; Sousa, Lucas Resende; Junior, Paulo Cézar Simamoto; Sousa, Gilmar da Cunha; Neto, Alfredo Júlio Fernandes (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Temporomandibular dysfunction (TMD) is a collective term adding up the entire problems related to temporomandibular joint (TMJ) and the mandibular functional impairment is one of the symptoms of TMD. It is known that the posture influences the onset of TMD, thus, as in the appearance of mandibular functional impairment. Dentists remain in inadequate positions during their workday, thus presenting an important risk factor for the onset of TMD. Objective: To classify temporomandibular dysfunction and mandibular functional impairment in undergraduates of the 8th period of the Dentistry course in the “Centro Universitário do Triângulo-UNITRI”, in Uberlândia, MG, Brazil. Methodology: This is a cross-sectional, practical, exploratory with a quantitative approach, epidemiological study carried out through application of two questionnaires: Mandibular Functional Impairment Index (MFIQ) and Clinical Dysfunction Index (IDCCM or Helkimo Index). Results: The results found in the present study showed a higher prevalence of moderate TMD (70,83%), followed by mild TMD (16.67%) and severe TMD (12,50%) and all participants were classified with mandibular functional impairment of low severity. Conclusion: The results of this research showed a high prevalence of moderate TMD in dentistry students and that there is no correlation between TMD and mandibular functional impairment. It was observed that many students had pain in the neck and/or shoulder.